PENDIDIKAN KARAKTER BANGSA ANTARA CITA-CITA DAN REALITA - Fiki Adelia Stefani; Nadila Meylina (Jurnal Ilmiah Multidisiplin Ilmu, 2024)
Education becomes the focal point in the context of nation building. However, between the idealized aspirations and the realities that unfold, there are portrayals that need to be seriously considered. This paper aims to explore the dynamics of character education in Indonesia, examining the disparities between ideals and realities. Firstly, this paper will delineate the ideal aspirations in character education which encompass moral values, ethics, and strong leadership. Subsequently, challenges and obstacles that arise in the implementation of character education amidst a complex and diverse society will be elucidated. Towards the conclusion, the paper will highlight the portrayal of the disparities between aspirations and realities existing within character education in Indonesia. This research adopts a qualitative approach, delving into data from various sources such as literature, case studies, and interviews with education experts and relevant stakeholders. In-depth analysis will be conducted to comprehensively depict the current condition of character education. Findings from this research are expected to provide valuable insights for stakeholders in improving the nation's character education system. By understanding the portrayal of aspirations and realities, concrete steps can be taken to enhance the effectiveness of character education and realize the ideal vision of nation building.